Survival Analysis of Penile Cancer Patients Using Cox-Proportional Hazard and GPT-4 - Wiwik Wiyanti (Department of Mathematics, Hasanuddin University, 2024)
Today, in 2024, the evolution of the evolution of artificial intelligence (AI) is very impressive. An AI product that continues to develop is ChatGPT. The threat of ChatGPT to some job professions is real. Beside that, ChatGPT also helps many professions make their work easier. In this research, we analyze the survival analysis of penile cancer patients. The design of this research is mixed-method (quantitative-qualitative). The quantitative and qualitative methods that were used are Cox-proportional hazards and GPT-4, respectively. Based on quantitative analysis, it can be concluded that the Survival and Hazard model for study penile cancer are and , respectively. The predicted chances of survival and death for the patient in stage 2, 14 days after surgery, are 40% and 60%, respectively. Based on qualitative analysis, GPT-4 cannot quantitatively obtain the cox proportional hazard number. However, even so, GPT4 can read the cox proportional hazard output image, providing Python and R survival analysis coding quite perfectly. Thus, the qualitative method's conclusion is that GPT-4 can greatly assist data analysts in their analysis of survival data.